2018
DOI: 10.2174/1566523218666181109141257
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-Grade Oncolytic Adenovirus Purification Using Polysorbate 20 as an Alternative for Cell Lysis

Abstract: Introduction: Oncolytic virus therapy is currently considered as a promising therapeutic ap-proach for cancer treatment. Adenovirus is well-known and extensively characterized as an oncolytic agent. The increasing number of clinical trials using this virus generates the demand for the development of a well-established purification approach. Triton X-100 is commonly used in cell lysis buffer prepara-tions. The addition of this surfactant in the list of substances with the very high concern of the Registra-tion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
(34 reference statements)
1
26
0
Order By: Relevance
“…At large scale production, chemical lysis is the strategy of choice, as opposed to homogenization, and is usually done by the addition of low concentrations of surfactants (0.1% Triton X-100 or NP-40) [52][53][54]. More recently, Triton X-100 was included on the list (Annex XIV) of Registration, Evaluation, Authorization, and Restriction of Chemicals (REACH), prohibiting its use from 4 January 2021, leading to the evaluation of different cell lysis detergents [55]. However, when adding surfactants, or even other reagents to the culture, they should be removed or reduced later to decrease the impact on the performance of the next unit operations.…”
Section: Harvest and Clarificationmentioning
confidence: 99%
See 1 more Smart Citation
“…At large scale production, chemical lysis is the strategy of choice, as opposed to homogenization, and is usually done by the addition of low concentrations of surfactants (0.1% Triton X-100 or NP-40) [52][53][54]. More recently, Triton X-100 was included on the list (Annex XIV) of Registration, Evaluation, Authorization, and Restriction of Chemicals (REACH), prohibiting its use from 4 January 2021, leading to the evaluation of different cell lysis detergents [55]. However, when adding surfactants, or even other reagents to the culture, they should be removed or reduced later to decrease the impact on the performance of the next unit operations.…”
Section: Harvest and Clarificationmentioning
confidence: 99%
“…PES membrane cassettes of 100 or 300 kDa have also been used for lentiviral vectors concentration allowing 66-fold concentration with complete vector recovery [83]. The use of Hollow-fibres devices can result in lower shear rates when compared with membrane cassette devices and have been used in the manufacturing of several viral particles -Adenovirus, Influenza virus, rotavirus like particles and HIV VLPs [53,55,60,63]. Regarding extracellular vesicles, PES or RC membrane devices with 100 kDa have been used, but their behavior in the purification of these particle has not been fully explored yet [76,84,86].…”
Section: Intermediate Purificationconcentration and Chromatographymentioning
confidence: 99%
“…73 It is easy to scaleup; however, recent research has shown that Triton X-100 has created some acute oral toxicity, eye damage, skin irritation, and chronic aquatic toxicity. 74 As a result, the detergent was listed as the substance of very high concern (SVHC) in December 2016 by the European Chemicals Agency under REACH regulations after several years of debate regarding its safety. 74 Therefore, an alternative cell lysis method is needed that is not only able to lyse cells, but can also protect AAV vectors from various stresses during the purification process.…”
Section: Challenges In Downstream Processingmentioning
confidence: 99%
“…This selection had in consideration the fact that although working with a chromatographic media with a lower DBC the impact in current work of using a convective media would be mainly in terms of volumetric productivity. Besides, keeping the current chromatography media (Capto Q ImpRes) enabled us to benchmark the current strategy against our previous study (Moleirinho et al, 2018).…”
Section: Resin Evaluation and Breakthrough Modelingmentioning
confidence: 99%